A Pull-in Based Test Mechanism for Device Diagnostic and Process Characterization - L. A. Rocha (2008)
A test technique for capacitive MEMS accelerometers and electrostatic microactuators, based on the measurement of pull-involtages and resonance frequency, is described. Using this combination of measurements, one can estimate process-inducedvariations in the device layout dimensions as well as deviations from nominal value in material properties, which can be usedeither for testing or device diagnostics purposes. Measurements performed on fabricated devices conrm that the 250 nm overetchobserved on SEM images can be correctly estimated using the proposed technique.